2020
DOI: 10.1038/s41467-020-18474-w
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba and Giardia parasites implicated as hosts of CRESS viruses

Abstract: Metagenomic techniques have enabled genome sequencing of unknown viruses without isolation in cell culture, but information on the virus host is often lacking, preventing viral characterisation. High-throughput methods capable of identifying virus hosts based on genomic data alone would aid evaluation of their medical or biological relevance. Here, we address this by linking metagenomic discovery of three virus families in human stool samples with determination of probable hosts. Recombination between viruses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 77 publications
2
46
0
Order By: Relevance
“…To date, some studies have shown that certain CRESS-DNA viruses (like circovirus) may be related to animal diseases [64,65], but it is not clear whether these viruses can infect mammalian cells and directly cause calf diarrhoea. Recently, a high-throughput approach to identifying viral hosts using genomic data alone will help us address this challenge in the future [63]. In this study, most of the reads related to smacovirus, circovirus and other unclassified CRESS-DNA viruses were detected in the healthy group.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…To date, some studies have shown that certain CRESS-DNA viruses (like circovirus) may be related to animal diseases [64,65], but it is not clear whether these viruses can infect mammalian cells and directly cause calf diarrhoea. Recently, a high-throughput approach to identifying viral hosts using genomic data alone will help us address this challenge in the future [63]. In this study, most of the reads related to smacovirus, circovirus and other unclassified CRESS-DNA viruses were detected in the healthy group.…”
Section: Discussionmentioning
confidence: 81%
“…CRESS-DNA viruses are ubiquitous in the virome of many ecosystems and have been suspected of infecting a wide range of organisms such as vertebrates, plants, fungi, and diatoms [60][61][62][63]. To date, some studies have shown that certain CRESS-DNA viruses (like circovirus) may be related to animal diseases [64,65], but it is not clear whether these viruses can infect mammalian cells and directly cause calf diarrhoea.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the bootstrap value between unclassified CRESS DNA viruses and other viruses was 100, indicating that these newly discovered viruses shared common characteristics with the previously studied viruses. Recently, it has been suggested that parasites may be potential hosts for CRESS DNA viruses; however, the parasite genomes did not actually contain CRESS endogenous viral elements ( 30 ). Coincidentally, a sequence of Giardia intestinalis was indeed found in the FeSCV genome.…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, computational methods for identifying hosts of metagenomic virus species are needed. To illustrate one approach, we describe the recent discovery of three circular Rep-encoding single-stranded (CRESS) DNA virus families (phylum Cressdnaviricota) in human clinical samples, and the determination of their hosts, being pathogenic human gut parasites [65]. In that study, host determination was achieved by (1) identifying recombination events between viral genomes to delimit groups overlapping in their host range, and (2) linking groups to a specific host or higher level taxon using endogenous viral elements in host genomes (see Figure 8), host small RNAs, and a case-control based examination of clinical samples.…”
Section: Recombination Network and Endogenous Viral Anchors For High-throughput Hostmentioning
confidence: 99%